2021
DOI: 10.1200/jco.2021.39.15_suppl.2633
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor use (PPI) in patients treated with immune checkpoint inhibitors (ICI) for advanced cancer: Survival and prior therapy.

Abstract: 2633 Background: Emerging data suggest that concomitant medications (CM) influence response to ICI. CM impact the host microbiome which may mitigate tumor-immune responsiveness. PPI use in patients treated with ICI has been associated with worse survival. Few data exist regarding the effects of PPI use in terms of prior chemotherapy or in risk for immune related adverse events (irAE) (e.g., colitis). Methods: This retrospective study of patients with advanced cancer treated with ICI between 2011 and 2019 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Finally, 33 studies, of which 24 were peer-reviewed journal publications and 9 were conference abstracts, were included in the systematic review and meta-analysis. 12 , 13 , 19 49 The flow diagram of identifying the eligible studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 33 studies, of which 24 were peer-reviewed journal publications and 9 were conference abstracts, were included in the systematic review and meta-analysis. 12 , 13 , 19 49 The flow diagram of identifying the eligible studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Another explanation is that we cannot exclude a negative impact of the IDC leading to accelerated tumor growth. For instance, recent studies across a broad variety of cancers have suggested that proton pump inhibitors could negatively affect outcomes in ICI-treated patients [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, the remaining studies were further screened by excluding reviews or meta-analyses (n = 41), studies with unavailable results (n = 8), studies unrelated with solid tumors (n = 5), and non-clinical studies (n = 6). Finally, a total of 17 articles published between January 2016 and July 2021 were included in our meta-analysis [ (12,15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)].…”
Section: Study Selectionmentioning
confidence: 99%